Strategic Analysis of PRACTO - Khosla, Kunaal; Kubíček, Aleš; Pernica, Karel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis aims to analyze Practo's strategic position within the global healthcare technology ecosystem using various strategic management tools and to formulate strategic recommendations for its growth and sustainability. The study employs SWOT analysis, PEST analysis, and Porter's Five Forces model to evaluate Practo's competitive environment, market strategy, and development prospects. Additionally, financial benchmarking and the VRIO framework are used to assess Practo's resources, competencies, and financial stability in comparison to key competitors such as 1mg, Mfine, and Pharmeasy. The analysis reveals significant insights into Practo's strengths, weaknesses, opportunities, and threats, as well as the broader macroenvironmental factors influencing its operations. The study concludes with strategic recommendations aimed at enhancing Practo's operational efficiency, diversifying revenue streams, strengthening customer engagement, expanding market reach, and investing in technological innovation. These recommendations are designed to help Practo navigate the competitive landscape and achieve sustainable growth in the rapidly evolving digital health market.
Vedoucí práce: Aleš Kubíček
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses